2017
DOI: 10.1177/1687814017716619
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical analysis of a single degree-of-freedom impact oscillator with impulse excitation

Abstract: In this article, the dynamical behavior of a single degree-of-freedom impact oscillator with impulse excitation is studied, where the mass impacts at one stop and is shocked with impulse excitation at the other stop. The existing and stability conditions for periodic motion of the oscillator are established. The effects of system parameters on dynamical response are discussed under different initial velocities. It is found that smaller shock gap than impact gap could make the periodic motion more stable. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…From the analysis of two-parameter bifurcation diagrams and basins of attraction, they found that the key factor to realize such control objective is to suppress the period-3 solutions that coexist with the desired small amplitude period-1 motions. Wang et al [50] investigated the dynamical behavior of a single degree-of-freedom impact oscillator that impacts at one stop and is shocked with impulse excitation at the other stop and established the existing and stability conditions for period-1 motion of the oscillator and its properties. Furthermore, they discussed the effects of system parameters on dynamical response under different initial velocities.…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis of two-parameter bifurcation diagrams and basins of attraction, they found that the key factor to realize such control objective is to suppress the period-3 solutions that coexist with the desired small amplitude period-1 motions. Wang et al [50] investigated the dynamical behavior of a single degree-of-freedom impact oscillator that impacts at one stop and is shocked with impulse excitation at the other stop and established the existing and stability conditions for period-1 motion of the oscillator and its properties. Furthermore, they discussed the effects of system parameters on dynamical response under different initial velocities.…”
Section: Introductionmentioning
confidence: 99%
“…The mitigation of pounding induced by earthquake between steel structures through the interposition of shock absorbers between the colliding members are the focus of the papers. 15,16,[25][26][27][28][29][30] The constitutive relations between impacting systems can be modeled in different ways. A summary subdivision can be made in two general groups: hard and soft impacts.…”
Section: Impact By Bumpersmentioning
confidence: 99%
“…Wang et al, 26 Mate et al, 28 Bamer et al, 29 Wang et al, 30 and Crozet et al 16 presented numerical studies devoted to the analysis of building pounding for SDOF 16,26,30 and MDOF 28,29 (Bamer et al 29 in 2-D and Mate et al 28 in 3-D) systems, under seismic 16,28,29 and impulsive excitation. 26,30…”
Section: Impact By Bumpersmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of impact motion, and the bifurcations from one motion to the other, that can occur in the dynamics of vibro-impact systems with motion limiting constraints, with the variation of selected parameters are the subject of several studies, of mainly numerical nature [47][48][49][50][51][52][53][54][55][56][57][58][59][60]. The study of the dynamics of a two-degree-of-freedom periodicallyforced system with symmetric motion limiting constraints, with emphasis on the transition between fundamental impact motions, together with the design and implementation of an electronic circuit, describing the dynamic characteristics of the non-smooth system, are presented in [52].…”
Section: Introductionmentioning
confidence: 99%